2015
DOI: 10.1371/journal.pone.0121128
|View full text |Cite
|
Sign up to set email alerts
|

The Nicotinic Receptor Alpha7 Impacts the Mouse Lung Response to LPS through Multiple Mechanisms

Abstract: The nicotinic acetylcholine receptor alpha7 (α7) is expressed by neuronal and non-neuronal cells throughout the body. We examined the mechanisms of the lung inflammatory response to intranasal (i.n.) lipopolysaccharide (LPS) regulated by α7. This was done in mice using homologous recombination to introduce a point mutation in the α7 receptor that replaces the glutamate residue 260 that lines the pore with alanine (α7E260A), which has been implicated in controlling the exceptional calcium ion conductance of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
58
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(62 citation statements)
references
References 39 publications
4
58
0
Order By: Relevance
“…Also notable was the reduction of inflammatory cell infiltration into the α7 E260A:G lung as measured in the bronchial alveolar lavage fluid (BALF) despite the relatively normal recruitment of inflammatory cells into the blood from the bone-marrow. Notably, in reciprocal chimeric mice constructed from bone marrow of differing α7 genotypes it was shown that the non-hematopoietic cells of the α7 E260A:G mouse lung dominated this overall inefficient LPS-response and the poor recruitment of bone-marrow derived inflammatory cells to the lung [14]. This study extends those findings to examine the α7 E260A:G CD45 - resident cell transcriptional responses to i.n.…”
Section: Introductionmentioning
confidence: 59%
See 4 more Smart Citations
“…Also notable was the reduction of inflammatory cell infiltration into the α7 E260A:G lung as measured in the bronchial alveolar lavage fluid (BALF) despite the relatively normal recruitment of inflammatory cells into the blood from the bone-marrow. Notably, in reciprocal chimeric mice constructed from bone marrow of differing α7 genotypes it was shown that the non-hematopoietic cells of the α7 E260A:G mouse lung dominated this overall inefficient LPS-response and the poor recruitment of bone-marrow derived inflammatory cells to the lung [14]. This study extends those findings to examine the α7 E260A:G CD45 - resident cell transcriptional responses to i.n.…”
Section: Introductionmentioning
confidence: 59%
“…Pharmacological agents specific to α7 suppress the response to LPS [7,10], a result that was confirmed and extended in the lung of α7 E260A:G mice [14]. In the α7 E260A:G mouse the inflammatory response by both hematopoietic and local non-hematopoietic cells to intranasal (i.n.)…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations